Anthracycline resistance mediated by reductive metabolism in cancer cells: the role of aldo-keto reductase 1C3 - Hofman, Jakub; Malcekova, Beata; Skarka, Adam; Novotna, Eva; Wsol, Vladimir (Toxicology and applied pharmacology, 2014)
Pharmacokinetic drug resistance is a serious obstacle that emerges during cancer chemotherapy. In this study, we investigated the possible role of aldo-keto reductase 1C3 (AKR1C3) in the resistance of cancer cells to anthracyclines. First, the reducing activity of AKR1C3 toward anthracyclines was tested using incubations with a purified recombinant enzyme. Furthermore, the intracellular reduction of daunorubicin and idarubicin was examined by employing the transfection of A549, HeLa, MCF7 and HCT 116 cancer cells with an AKR1C3 encoding vector. To investigate the participation of AKR1C3 in anthracycline resistance, we conducted MTT cytotoxicity assays with these cells, and observed that AKR1C3 significantly contributes to the resistance of cancer cells to daunorubicin and idarubicin, whereas this resistance was reversible by the simultaneous administration of 2'-hydroxyflavanone, a specific AKR1C3 inhibitor. In the final part of our work, we tracked the changes in AKR1C3 expression after anthracycline exposure. Interestingly, a reciprocal correlation between the extent of induction and endogenous levels of AKR1C3 was recorded in particular cell lines. Therefore, we suggest that the induction of AKR1C3 following exposure to daunorubicin and idarubicin, which seems to be dependent on endogenous AKR1C3 expression, eventually might potentiate an intrinsic resistance given by the normal expression of AKR1C3. In conclusion, our data suggest a substantial impact of AKR1C3 on the metabolism of daunorubicin and idarubicin, which affects their pharmacokinetic and pharmacodynamic behavior. In addition, we demonstrate that the reduction of daunorubicin and idarubicin, which is catalyzed by AKR1C3, contributes to the resistance of cancer cells to anthracycline treatment.
Keywords: 3-Hydroxysteroid Dehydrogenases; Drug Resistance, Neoplasm; Doxorubicin; Kinetics; Idarubicin; flavanony; Cell Line, Tumor; Metabolism; protinádorová antibiotika; Hydroxyprostaglandin Dehydrogenases; Enzyme induction; 3-hydroxysteroid dehydrogenasy; antracykliny; daunomycin; Enzyme Inhibitors; lidé; Drug resistance; rekombinantní proteiny; Recombinant Proteins; Anthracyclines; chemorezistence; Antibiotics, Antineoplastic; Carcinoma; Aldo-keto reductase 1C3; karcinom; oxidace-redukce; Oxidation-Reduction; biotransformace; inhibitory enzymů; protein AKR1C3; Drug Synergism; doxorubicin; Daunorubicin; nádorové proteiny; Neoplasm Proteins; synergismus léků; Enzyme Induction; enzymová indukce; Biotransformation; Cell Survival; idarubicin; viabilita buněk; Flavanones; Aldo-Keto Reductase Family 1 Member C3; kinetika; nádorové buněčné linie; hydroxyprostaglandindehydrogenasy; Humans